In Situ Generated Novel 1H MRI Reporter for β-Galactosidase Activity Detection and Visualization in Living Tumor Cells - Gao, Shuo; Zhao, Lei; Fan, Zhiqiang; Kodibagkar, Vikram D.; Liu, Li; Wang, Hanqin; Xu, Hong; Tu, Mingli; Hu, Bifu; Cao, Chuanbin; Zhang, Zhenjian; Yu, Jian-Xin (Frontiers in Chemistry, 2021)
For wide applications of lacZ gene in cellular/molecular biology, small animal investigations, and clinical trials, the development of non-invasive imaging approaches for better reliability, precision and accuracy to assay gene expression has attracted much attention. We now report a novel molecular platform, in which alizarin 2-O-β-D-galactopyranoside AZ-1 works as a lacZ gene/β-gal 1H MRI reporter to responsively and specifically generate significant 1H-MRI contrast changes in relaxation times T1 and T2 in situ as a concerted effect for detection of β-gal activity with the presence of Fe3+. We also demonstrate the feasibility of this strategy for assessing β-gal activity in solution and in vitro with lacZ transfected human MCF7 breast and PC3 prostate cancer cells by reaction-enhanced 1H-MRI T1 and T2 relaxation mapping.